2020
DOI: 10.1016/j.cropro.2019.104963
|View full text |Cite
|
Sign up to set email alerts
|

Changes in insecticide resistance and host range performance of planthoppers artificially selected to feed on resistant rice

Abstract: Host plant resistance has received considerable attention for the management of insect herbivores on crop plants. However, resistance is threatened by the rapid adaptation of target herbivores towards virulence (the ability to survive, develop and damage a host with major resistance genes). This study examines the potential costs and benefits of adaptation for virulence in herbivores. We continuously reared planthoppers, Nilaparvata lugens, on two susceptible and three resistant rice, Oryza sativa, varieties f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…PTB33 possesses at least two genes for resistance to the planthopper ( BPH32 and BPH26 [synonym with BPH2 ] 20 ). IR62 is a promising source of resistance for future rice breeding because it appears counter-selective for virulence against BPH1 and BPH2 22 . We used the variety IR22 as a susceptible control in our experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTB33 possesses at least two genes for resistance to the planthopper ( BPH32 and BPH26 [synonym with BPH2 ] 20 ). IR62 is a promising source of resistance for future rice breeding because it appears counter-selective for virulence against BPH1 and BPH2 22 . We used the variety IR22 as a susceptible control in our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The BPH32 gene encodes a protein with a signal peptide and SCR-domain that likely binds to planthopper glycoproteins or tissues to inhibit feeding 20 . Selection studies have further shown that planthoppers adapted to feed on IR62 will gain virulence against the resistant variety Rathu Heenati 21 , 22 . Such virulence-adapted planthoppers often possess relatively high densities of yeast-like symbionts (YLS) compared to non-virulent planthoppers feeding on susceptible varieties, which may compensate for the effects of anti-feedants 21 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Horgan et al (2016) [ 37 ] found that ca 80% of the non-adapted nymphs that survive feeding on IR62 are females and, among these, between 20–50% can have swollen abdomens—indicating potentially high reproductive output [ 37 ]. Nevertheless, egg laying and population build-up are often severely inhibited on IR62, even where planthoppers appear otherwise adapted to feed and grow on the variety—as seen in this study ( Table 1 ) and indicated in a further selection study using the same IR62-planthopper system [ 39 ]. These observations suggest that virulence adaptation results from a combination of adapted traits working on different aspects of the planthopper’s complete life cycle.…”
Section: Discussionmentioning
confidence: 69%
“…Our planthoppers also demonstrated partial adaptation to IR62 (they survived and developed well but were inefficient feeders and had slow population growth). Partial virulence may be of little benefit to planthoppers and leafhoppers that cannot build up populations in the field because of poor egg-laying capacity on a resistant host—as demonstrated in this and other studies [ 39 ]. However, even partial resistance seems to be stable in populations that are returned for several generations to a susceptible host [ 9 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation